Gliogenesis depends on glide/gcm through asymmetric division of neuroglioblasts. - Bernardoni, R.; Kammerer, M.; Vonesch, J.L.; Giangrande, A. (Developmental Biology, 1999)
Some neurons and glial cells originate from neuroblasts and glioblasts, stem cells that delaminate from the ectoderm of developing fly embryos. A second class of glial cells and neurons differentiates from multipotent precursors, the neuroglioblasts. The differentiation of both glial cell types depends on glial cell deficient/glial cell missing (glide/gcm). Although it has been shown that this transcription factor promotes gliogenesis at the expense of neurogenesis, the cellular mechanisms underlying this fate choice are poorly understood. Using loss and gain of function glide/gcm mutations here we show that the cell fate choice takes place in the neuroglioblast, which divides and produces a glioblast and a neuroblast. Such choice requires the asymmetric distribution of glide/gcm RNA, which accumulates preferentially on one side of the neuroglioblast and is inherited by one cell, the presumptive glioblast. Interestingly, glial cells can differentiate from cells that delaminate as neuroglioblasts or they can arise from cells that start expressing glide/gcm several hours after delamination of a neuroblast. Altogether, these findings identify a novel type of asymmetric cell division and disclose the lineage relationships between glia and neurons. They also reveal the mode of action of the glide/gcm promoting factor.